Western teachers in teaching speaking skill of English as a foreign language - Benefits and challenges from perspectives of students: a survey research at an English Language Center in Cantho city : - Hồ, Thị Kim Thanh (Trường Đại học Cần Thơ, 2013)
The research findings revealed that almost all participants agreed that they have a lot benefits when they are taught by Western teachers.